2022
DOI: 10.1002/csc2.20757
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of soybean genotypes to off‐target dicamba damage

Abstract: Since the commercialization and widespread adoption of dicamba-tolerant (DT) soybean cultivars across the United States, numerous cases of off-target damage to non-DT soybean have been reported. Soybean is naturally highly sensitive to dicamba, a synthetic auxin herbicide. Previous studies have focused on understanding the impact of growth stage, dosage, frequency, and duration of dicamba exposure on the severity of symptomology and yield loss. To date, little research has investigated the effect of genetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…The number of susceptible plots accounted for 13.4% (309 plots) in 2020 and 9.2% (132 plots) in 2021, and the number of tolerant plots accounted for 10.7% (245 plots) in 2020 and 22.1% (316 plots) in 2021. The distribution of plot numbers in three categories was aligned with the breeder’s expectation that most soybean genotypes have a moderate response to off-target dicamba damage, which is consistent with the findings of [ 40 ]. Conventional breeding programs usually select 10% of genotypes to be advanced throughout the pipeline based on their observations.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The number of susceptible plots accounted for 13.4% (309 plots) in 2020 and 9.2% (132 plots) in 2021, and the number of tolerant plots accounted for 10.7% (245 plots) in 2020 and 22.1% (316 plots) in 2021. The distribution of plot numbers in three categories was aligned with the breeder’s expectation that most soybean genotypes have a moderate response to off-target dicamba damage, which is consistent with the findings of [ 40 ]. Conventional breeding programs usually select 10% of genotypes to be advanced throughout the pipeline based on their observations.…”
Section: Resultssupporting
confidence: 85%
“…According to Ref. [ 40 ], the observed trend of higher tolerance to off-target dicamba damage among the genotypes could be explained by the indirect selection process employed in conventional breeding pipelines. Conventional breeding programs prioritized various breeding trials with favorable agronomic traits and higher yields in environments with prolonged exposure to dicamba.…”
Section: Resultsmentioning
confidence: 99%
“…The two center rows of each plot were used to evaluate the agronomic data and were harvested for yield with a plot combine. To minimize the noise in the yield data caused by the prolonged off‐target dicamba (3,6‐dichloro‐2‐methoxybenzoic acid) exposure, cooperative yield trials (COOPs) were conducted in 2018 and 2020 (Vieira, Sarkar, et al., 2022; Vieira, Zhou, et al., 2022). Nonreplicated, randomized COOPs were conducted at seven environments, including two in Arkansas and one environment each in Louisiana, Missouri, Mississippi, Tennessee, and Virginia, in 2018, and S5503GT was evaluated in five environments including two in Arkansas and one environment each in Louisiana, Mississippi, and Tennessee in 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Soybean is highly sensitive to dicamba. Symptoms of dicamba exposure include crinkling and cupping of immature leaves, decreased plant height, apical meristem death, abnormal pod formation, and reduced grain yield ( Weidenhamer et al., 1989 ; Andersen et al., 2004 ; Grossmann, 2010 ; Kniss, 2018 ; Canella Vieira et al., 2022b ). Timing, dosage, frequency, and duration of exposure have been shown to affect the severity of the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, soybean is far more sensitive to dicamba exposure at the early reproductive stage relative to the vegetative stage ( Egan et al., 2014 ; Solomon and Bradley, 2014 ; Soltani et al., 2016 ; Kniss, 2018 ). Recently, different genetic backgrounds were reported to also influence the intensity of symptomology resulting from off-target dicamba in soybean ( Canella Vieira et al., 2022b ). That study reported differential responses of conventional soybean genotypes to off-target dicamba, where certain genetic backgrounds showed consistently superior responses with minimal symptoms and yield losses under prolonged off-target dicamba exposure ( Canella Vieira et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%